2017
DOI: 10.1097/brs.0000000000001687
|View full text |Cite
|
Sign up to set email alerts
|

Defensive Medicine in U.S. Spine Neurosurgery

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 19 publications
0
30
0
Order By: Relevance
“…While we have attempted to isolate the effect of non-economic damages in our methods, the contributors to defensive practice are complex and interwoven. The clinical decision making of these specialized practitioners may be influenced by perception that they are targets for lawsuits [27], bias from the referral nature of their practices, specialty-based differences in treatment of LBP, and behaviors instilled from training or practice [10]. Our sensitivity analysis (with MRI and CT scans isolated) demonstrates that both the timing and type of test ordered are preference-sensitive, further showing the influence of individual practice.…”
Section: Discussionmentioning
confidence: 86%
“…While we have attempted to isolate the effect of non-economic damages in our methods, the contributors to defensive practice are complex and interwoven. The clinical decision making of these specialized practitioners may be influenced by perception that they are targets for lawsuits [27], bias from the referral nature of their practices, specialty-based differences in treatment of LBP, and behaviors instilled from training or practice [10]. Our sensitivity analysis (with MRI and CT scans isolated) demonstrates that both the timing and type of test ordered are preference-sensitive, further showing the influence of individual practice.…”
Section: Discussionmentioning
confidence: 86%
“…Similar results were also seen in more recent surveys focused on practicing defensive medicine in the neurosurgical field. 8,11,12 In the study by Smith et al, neurosurgeons in the US were 50% more likely to practice defensive medicine in states categorized as high-risk liability environments than in states categorized as low-risk liability environments. 12 Another survey among US neurosurgeons showed that neurosurgeons who mainly practice spine surgery were up to three times more likely to practice defensive medicine than other neurosurgeons.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…12 Another survey among US neurosurgeons showed that neurosurgeons who mainly practice spine surgery were up to three times more likely to practice defensive medicine than other neurosurgeons. 11 In contrast to earlier studies in which neurosurgeons employed in the US had been surveyed, Yan et al explored defensive medicine behaviors among Dutch neurosurgeons. 8 Their study showed that Dutch neurosurgeons viewed their practices to be less at risk in general compared to their American colleagues.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The other interests of this alternative route are to counteract defensive practices by trying to reduce and control insurance and legal costs for the parties (in fact, lawyers are not necessarily involved in CCI procedures). 3,23,24 In addition, no-fault schemes make it easier to communicate and think about the identification and prevention of adverse events. 25,26…”
Section: National Solidarity and The Welfare Statementioning
confidence: 99%